PRODUCTIVE BEHAVIOR OF A LOT OF HENS POSITION vaccinated with strain of Mycoplasma gallisepticum ts11 - Sánchez I., Roxana (2005)
A field study was conducted to evaluate productive parameters in layers vaccinated with the Mycoplasma gallisepticum (MG) ts11 vaccine. A total of 9,065 free mycoplasma Hy Line Brown pullets were raised on a previously detected MG positive farm. The birds were divided in two groups and placed in two separated sections in the same farm. One group was vaccinated at four weeks of age and the other remained non vaccinated. Serum plate agglutination (SPA), haemagglutination inhibition (HI) and enzyme linked immunsorbent assay (ELISA) were used to measure the serum antibody response after vaccination and field challenges. Polymerase chain reaction assay (PCR) and cultures were used to determine field challenges by mycoplasma and salmonella. Vaccinated birds laid 188 egg/hen (11.55 kg) whereas non-vaccinated ones laid 184 egg/hen (11.34 kg) over a 41-week period. Feed conversion was 2.57 and 2.62 for the vaccinated and the nonvaccinated group respectively (p<0.05). There were significant differences in the productive parameters between vaccinated and non vaccinated group. The marginal economic analysis showed an economic profit of S/. 1.50 (US$ 0.43) per housed hen. The birds were exposed to environmental heat stress and natural challenges by Mycoplasma gallisepticum, Mycoplasma synoviae, infectious bronchitis virus and Salmonella enteritidis. Despite the negative influence of these factors on the productive performance, the results of this study showed an economic profit and better productive results after vaccination with the ts11 strain.